Correction: Selenium effects on the metabolism of a Se-metabolizing Lactobacillus reuteri: analysis of envelope-enriched and extracellular proteomes. Issue 2 (10th April 2018) - Pessione, E.; Lamberti, C.; Pessione, A.; Galano, E.; Amoresano, A.; Mangiapane, E.
Abstract : Correction for 'Selenium effects on the metabolism of a Se-metabolizing Lactobacillus reuteri : analysis of envelope-enriched and extracellular proteomes' by E. Mangiapane et al., Mol. BioSyst., 2014, 10, 1272–1280.